"Cresceu como um renovo" (Is.53,20): o sistema simbólico ritual judaico do tempo de Jesus, uma das principais raízes do cristianismo - Carvalho, Glacilda Soares da Silva (2009)
The theme the jewish ritual symbolic system from Jesus‟ time, one of the primitive Christianity‟s main roots and its self-affirmation as religion involves an analysis of the ritual elements which guided the Judaism from the Jesus‟ time and that was used as a base to the primitive Christianity appearance. This work will consider the jewish religious cultural system from the first century of the Christian time and how it influenced the ritual symbolic system of primitive Christian signs, which begings with Jesus Himself. We are going to start with an approach about the religion, searching a huge vision of the cultural phenomenon and the religion function. The main focus turns around three poles: The jewish ritual symbolic system from the Jesus‟ time, as one of the primitive Christianity‟s main roots, the importance of the historical Jesus to the raise of the primitive Christian religion and the transformation of the jewish religion through the post-paschal faith in Christ. The historical Jesus is, from the post-paschal faith on, the presence of the primordial creator and the eschatological judge. He is one with God. The primitive Christian religion, from that time on, is going to find ways to become an autonomous religion, reusing the essence of the ritual symbolic system of jewish signs, and giving them a new meaning from Jesus on